2010
DOI: 10.1901/jaba.2010.43-125
|View full text |Cite
|
Sign up to set email alerts
|

Manipulating Slot Machine Preference in Problem Gamblers Through Contextual Control

Abstract: Pathological and nonpathological gamblers completed a task that assessed preference among 2 concurrently available slot machines. Subsequent assessments of choice were conducted after various attempts to transfer contextual functions associated with irrelevant characteristics of the slot machines. Results indicated that the nonproblem gambling group, but not the problem gambling group, increased their responding toward the slot initially trained as greater than following the initial training procedure, then de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
12
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 11 publications
2
12
0
Order By: Relevance
“…As well, the participants from the RT + D group demonstrated greater matched responding compared to the RT group, suggesting that following relational training designed to elaborate upon the participants' relational network for each color, the participants responded closer to the actual contingencies as predicted by the matching law. These results replicate the results reported in previous research (Hoon et al, ; Nastally et al, ; Zlomke & Dixon, ) by showing how a conditional discrimination relational training exercise can bring gambling behavior under contextual control of arbitrary variables in a concurrent schedules experimental arrangement. This line of research lends further support for the position that gambling behavior may be influenced by verbal relations that interact with direct‐acting contingencies.…”
Section: Discussionsupporting
confidence: 90%
“…As well, the participants from the RT + D group demonstrated greater matched responding compared to the RT group, suggesting that following relational training designed to elaborate upon the participants' relational network for each color, the participants responded closer to the actual contingencies as predicted by the matching law. These results replicate the results reported in previous research (Hoon et al, ; Nastally et al, ; Zlomke & Dixon, ) by showing how a conditional discrimination relational training exercise can bring gambling behavior under contextual control of arbitrary variables in a concurrent schedules experimental arrangement. This line of research lends further support for the position that gambling behavior may be influenced by verbal relations that interact with direct‐acting contingencies.…”
Section: Discussionsupporting
confidence: 90%
“…There is a literature on response allocation in concurrent slot machines, but findings in this area have been mixed; a number of studies (Coates & Blaszczynski, 2014;Daly et al, 2014;Dixon, Fugelsang, MacLaren, & Harrigan, 2013;Dixon, MacLin, & Daugherty, 2006;Dymond, McCann, Griffiths, Cox, & Crocker, 2012;Zlomke & Dixon, 2006) found evidence consistent with matching, but there is also evidence gamblers undermatch, showing greater (or in some cases, total) equivalence between machines that diverge either in rate of return to player or rate of reinforcement on a ratio schedule (Coates & Blaszczynski, 2013;Daly et al, 2014;Lucas & Singh, 2012;Weatherly, Thompson, Hodny, Meier, & Dixon, 2009). In addition, matching is highly susceptible to being overridden by contextual cues (Nastally, Dixon, & Jackson, 2010;Zlomke & Dixon, 2006) although this appears to weaken with extended exposure to the contingencies of a machine (Hoon & Dymond, 2013). Furthermore, there are some situations such as on multiple line slot machines where the rate of reinforcement can be (and is) controlled by the player while the rate of return remains the same (MacLaren, 2015).…”
Section: Behavioural Mechanismsmentioning
confidence: 99%
“…As demonstrated by Dixon et al (2003), pathological gamblers tend toward more impulsive choices than control participants and thus may respond to risk scenarios, rules, or outcomes differently than those without an extended history of gambling. One study attempted to use a relational training procedure to bias gamblers' responding to one of two concurrently available colored slot machines by training that one color was greater than the other, and found that nonpathological gamblers predictably shifted responding to the machine of the Bgreater^color while pathological gamblers continued to respond unpredictably (Nastally et al 2010). These results suggest that the effects observed when studying nonpathological samples may not generalize to pathological gamblers.…”
Section: Populationsmentioning
confidence: 99%